Pengaruh Dukungan Sosial Teman Sebaya terhadap Resiliensi Akademik Mahasiswa UIN Syarif Hidayatullah Jakarta - Melani, Dian Puspita; Solihin, Muhtar Mochamad (Jurnal Penyuluhan Agama, 2025)
Abstract: Final year students need to have good academic resilience, this can happen if there is social support from outside parties, one of which is social support from peers. Therefore, the objectives of this research are: 1. To describe the level of academic resilience of final students at the Faculty of Da'wah and Communication Sciences, UIN Syarif Hidayatullah Jakarta, 2. To analyze the influence of the variable (X) Peer Social Support on the variable (Y) Academic Resilience of Students at the Faculty of Da'wah and Communication Sciences. This research approach uses the Quantitative Correlational Method with a sample size of 85 students from the Faculty of Da'wah and Communication Sciences, UIN Syarif Hidayatullah Jakarta. The data analysis techniques used in this research are the Kolmogrov Smirnov normality test, simple linear test, correlation coefficient test, coefficient of determination test, T hypothesis test (partial), and F hypothesis test (simultaneous) using the SPSS Statistics 20 application. Social Support from Peers' Social Friends influences Academic Resilience so that Ha is accepted. The results of this research show: 1) The level of peer social support on academic resilience is 0.410, which is classified as a moderate correlation and has a positive value, 2) There is a significant influence between the social support variable of peers on the academic resilience variable of students in the faculty of da'wah and communication sciences with a value of Tcount (4.091) > Ttable (1.989), meaning that the higher the social support of peers, the higher the academic resilience of students in the faculty of Da'wah and communication sciences at UIN Syarif. Hidayatullah Jakarta.Abstrak: Mahasiswa tingkat akhir perlu memiliki resiliensi akademik yang baik, hal tersebut dapat terjadi apabila ada dukungan sosial dari pihak luar salah satunya yaitu dukungan sosial teman sebaya. Oleh karena itu tujuan dari penelitian ini : 1. Untuk mendeskripsikan tingkat Resiliensi Akademik Mahasiswa Akhir Fakultas Dakwah dan Ilmu Komunikasi UIN Syarif Hidayatullah Jakarta, 2. Untuk menganalisis pengaruh variabel (X) Dukungan Sosial Teman Sebaya Terhadap Variabel (Y) Resiliensi Akademik Mahasiswa Fakultas Dakwah dan Ilmu Komunikasi. Pendekatan penelitian ini menggunakan Metode Kuantitatif Korelasional dengan jumlah sampel 85 Mahasiswa Fakultas Dakwah dan Ilmu Komunikasi UIN Syarif Hidayatullah Jakarta. Teknik analisis data yang digunakan penelitian ini adalah uji normalitas kolmogrov smirnov, uji linear sederhana, uji koefisien korelasi, uji koefisien determinasi, uji hipotesis T (parsial), dan uji hipotesis F (simultan) dengan menggunakan aplikasi SPSS Statistics 20. Dukungan Sosial Teman Sosial Teman Sebaya berpengaruh terhadap Resiliensi Akademik sehingga Ha di terima. Hasil penelitian ini menunjukkan : 1) Tingkat dukungan sosial teman sebaya terhadap resiliensi akademik sebesar 0,410 tergolong korelasi sedang dan memiliki nilai positif, 2) Terdapat pengaruh yang siginifikan antara variabel dukungan sosial teman sebaya terhadap variabel resiliensi akademik mahasiswa fakultas dakwah dan ilmu komunikasi dengan nilai Thitung (4,091) > Ttabel (1,989), artinya semakin tinggi dukungan sosial teman sebaya maka semakin tinggi resiliensi akademik mahasiswa fakultas dakwah dan ilmu komunikasi UIN Syarif Hidayatullah Jakarta.